Rice Fallow No-Till Sorghum Using Inorganic Fertilizers in Combination with Biofertilizer Consortium: Nutrient Uptake, Yield Attributes and Economics - Reddy, Kadapa Sreenivasa; Rao, Ch. Pulla; Luther, M. Martin; Prasad, P. R. K. (International Journal of Bio-resource and Stress Management, 2023)
A field investigation was carried out to study the influence of inorganic fertilizers along with biofertilizer consortium on the performance of sorghum under rice fallows at Agricultural College Farm, Bapatla, Acharya N. G. Ranga Agricultural University, Andhra Pradesh, India during rabi (December–April), 2018–19. There were 7 treatments tested in randomized block design (RBD) with 3 replications. Yield attributes, length of earhead (33.2 cm), number of filled grains earhead-1 (1359) and maximum protein content (9.1) were recorded higher in 125% RDF+biofertilizer consortium and remained significantly on par with 100% RDF+biofertilzers consortium treatment. Application of 125% RDF+ biofertilizer consortium application (T6) significantly increased grain and stover yields by (30.3%, 26.5%) respectively, compared to control. The same T6 treatment recorded highest nitrogen, phosphorus and potassium uptake at 30, 60, 90 DAS and at harvest in the grain and straw followed by T5 treatment. Significantly higher grain, stover, and biological yield were obtained with 125% RDF treatment compared to 75% and 50% RDF. Improvement in N, P and K uptake in grain by (53.0, 58.0 and 74.4%) and stover by (50.5, 51.8 and 50.1%) compared with control treatment. The highest gross returns (Rs. ` 71710 ha-1), net returns (`Rs. 43155 ha-1) and returns `-1 investment (1.88) was obtained with application of 125% RDF+Biofertilizer consortium treatment. When compared to other treatments, the use of 125% RDF+Biofertilizer consortium increased the production and provided economic benefits may be adapted as choice of viable alternative in the coastal Andhra Pradesh.